Fresno County Bar Association Law Day Luncheon: Judge Robert Coyle Speaker - Watkins, Howard::::::::: (1986)
Thomas Richey speaking at lectern for flag salute; Catherine Golden-Taylor, Judge Robert Coyle and Faye Coyle